The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/opo.12641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eye rotation and contact lens decentration on horizontal peripheral refraction

Abstract: Purpose Peripheral refraction is important in design of myopia control therapies. The aim was to investigate the influence of contact lens decentration associated with eye rotation on peripheral refraction in the horizontal visual field. Methods Participants were 10 emmetropes and 10 myopes in good general and ocular health. Right eyes underwent cycloplegic peripheral refraction, using a Grand‐Seiko WAM‐5500 Autorefractor, in 5° steps to ±35° eccentricities along the horizontal visual field. Targets were fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
3
15
1
Order By: Relevance
“…The gradual shift toward yellow colours at near distances reveals increasing accommodative lags. When measured off‐axis (bottom series of maps), the axial separation of the CL optics and the eye’s entrance pupil causes the parallax shift of the CL centre, introducing more peripheral CL optics in front of the pupil 29–31 . The off‐axis optics in combination with parallax introduce more complex defocus patterns across the pupil due to oblique astigmatism and coma associated with off‐axis optics 32,33 …”
Section: Resultsmentioning
confidence: 99%
“…The gradual shift toward yellow colours at near distances reveals increasing accommodative lags. When measured off‐axis (bottom series of maps), the axial separation of the CL optics and the eye’s entrance pupil causes the parallax shift of the CL centre, introducing more peripheral CL optics in front of the pupil 29–31 . The off‐axis optics in combination with parallax introduce more complex defocus patterns across the pupil due to oblique astigmatism and coma associated with off‐axis optics 32,33 …”
Section: Resultsmentioning
confidence: 99%
“…This reduction in plus power is an important observation that provides an explanation for reported hyperopic retinal defocus in some studies using this lens 14,26 . In a study by Jaisankar et al , 14 as expected for centre‐distance multifocal contact lenses, they showed an increase in relative peripheral myopia out to 20 degrees.…”
Section: Discussionmentioning
confidence: 78%
“…This reduction in plus power is an important observation that provides an explanation for reported hyperopic retinal defocus in some studies using this lens. 14,26 In a study by Jaisankar et al, 14 as expected for centre-distance multifocal contact lenses, they showed an increase in relative peripheral myopia out to 20 degrees. However, on the nasal visual field (temporal retina), there is a marked increase in relative peripheral hyperopia, attaining a maximum value of +2.00D at the 35-degree eccentricity.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations